Assessment of relative efficiency of COVID-19 vaccines granted emergency use authorization in India and their respective modes of delivery-an economic evaluation - Ray, Shomik; Singh, Alka; Singh, Ranjana (International Journal Of Community Medicine And Public Health, 2023)
Background: Effective public health interventions need to be assessed for efficiency in order to optimize results and justify investments especially under conditions of uncertainty and resource constraints. The COVID-19 pandemic has presented unprecedented situations where decisions had to be taken based on limited evidence available in order to save human lives. Vaccines have been identified to be the mainstay of the public health response to the pandemic. In India, nine vaccines have been granted emergency use authorization (EUA) and are being delivered through multiple modes. Efficiency of vaccine delivery needs to be established to maximize results and formulate policy in long run. Methods: This study will be conducted in Delhi and Bhubaneshwar. Two systematic reviews, a cross-sectional community survey and a complete economic evaluation using a decision tree model will be carried out to meet the study objectives. Data will be captured through computer assisted personal interviewing (CAPI) using CS pro software. Outcomes will be measured in lives saved and quality adjusted life years (QALYs) gained by vaccination. This will be the first study providing a detailed cost of COVID-19 vaccination and treatment segregated by government or private provider Conclusions: The study would establish the relative efficiency of each vaccine granted EUA over the other by their individual modes of delivery.